Leadership styles of school middle managers in secondary school: implication on education performance - Norhisham Mohd Kasim; Mohd Nazri Zakaria; Haryati Basran (Faculty of Entrepreneurship and Business,UMK, 2015)
A leadership style in educational context has been debated issue in this decade recently. Eventhough, it is a few studies on leadership styles of middle managers in secondary school with its effects on educational outcomes. Henceforth, this study was conducted with the aim to identify the leadership styles of school middle managers in secondary school in the district of Sabak Bernam. The descriptive study comprised 125 teachers (here after refers as middle managers) from five secondary schools in Sabak Bernam district were randomly selected. The study employed mixed method research design where data were collected via questionnaire survey and in- depth semi- structured interviews. A questionnaire were used is Multifactor Leadership Questionnaire (MLQ) were adapted from Bass & Avolio (1992). The quantitative data were analysed using Statistical Package for Social Sciences (SPSS) 17.00 version while the qualitative data were analysed deductively and inductively regarding to the research questions in order to trace emerging patterns. In order to see the types of leadership styles by middle managers in secondary schools, a frequency, percent, mean, standard deviation and T- test were used to test the data. The main findings of the study show that Transactional leadership style was the most preferred leadership style among school middle managers. Then it is followed by Transformational leadership style and Laissez- faire leadership style. Findings also indicated that there were no significant differences in leadership styles between males and females school middle managers in secondary schools. The analysis also depicted that there was no significant difference in leadership styles between novice and experienced school middle managers. Nevertheless, the findings revealed that there was a significant difference in the mean score for Laissez- faire leadership style between novice and experienced school middle managers. The findings imply that educational leaders need to be aware on their leadership styles as it is help to leader to build a good relation with the followers and retain a productive workforce. The overview of the evidence and findings of the study are used for some suggestions and recommendations for the future research.